Multiple Layer Closure of Myoma Bed in Laparoscopic Myomectomy - Jain, Nutan (Medknow Publications & Media Pvt Ltd, 2011)
OBJECTIVE: To assess the feasibility and outcome of laparoscopic myomectomy and multiple layer closure of the myoma bed, for management of myomas, at a tertiary care hospital. MATERIALS AND METHODS: From September 2005 to September 2010, 417 patients, with large and moderate size myomas, were managed by laparoscopic myomectomy. Indications were subfertility, menorrhagia, and abdominal mass. Preoperative evaluation included history, clinical examination, and sonographic mapping. The myomas were enucleated and retrieved laparoscopically. Myoma beds were sutured in multiple layers by endoscopic intracorporeal suturing. RESULTS: Three hundred and fifteen patients presented with subfertility, 45 with menorrhagia, and 57 with abdominal mass. The average maximum diameter of a myoma was 9 cm. The mean duration of surgery was 120 minutes. The mean postoperative stay was 24 hours. No intraoperative complication occurred and the hospital course was uncomplicated. In one case, a minilap incision was performed for retrieval of the myoma with suturing of the bed. Two patients had minor delayed wound healing of the morcellator port site. The patients did not report any complaints during the follow-up, except one patient who developed omental hernia at the morcellator port site. There was no rupture of the scar and very low adhesion scores in the subsequent cesarean sections or second-look scopies. CONCLUSION: With proper multilayer closure of the myoma bed, laparoscopic myomectomy was feasible for moderate and even large myomas and had excellent outcomes.